Respostas
respondido por:
2
Observe que:
Onde,
a)
Temos e
Logo,
Desta maneira, as raízes são:
b)
As raízes são:
respondido por:
2
-x²+x+12=0 (R:-3, 4)
delta= 1^2 - 4.(-1).12 => 1+48 => 49
x= - 1+/-V49 => -1 +/- 7 => x1= -1+7 =>x1= 6 => x1= - 3
2.(-1) -2 -2 -2
x2= - 1 - 7 =>x2 = - 8 => x2 = 4
-2 -2
b) -x²+6x-5=0 (R:1,5)
delta= 6^2-4.(-1)(-5) = 36 - 20 = 16
x= -6 +/-V16 => -6 +/- 4 => x1 = -6 +4 => x1= -2 => x1 = 1
2.(-1) -2 -2 -2
x2= -6-4 => x2 = - 10 => x2 = 5
-2 - 2
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás